research competences and its relevance in the development of a doctoral thesis (Revista Electrónica REDINE, 2019)
The developed of a doctoral thesis requires for the part of the investigator some levels of knowledges, habilitys and actituds that allow generate contributions of a theoretical level to a certain field of knowledge. The strengthening of the investigative competence at a doctoral level inevitably merits on the part of the institutions to a permanent reflection and review about the elements o requirements that contribute to the development of a research with the purpose of a doctoral thesis. The objective of this review article is the reflection about the relevance of the investigative competence in the development of a doctoral thesis, as the set of dimensions and attributes coupled in the investigator that allow him direct their knowledge and perspectives in the different investigation works with looks of strengthen and orient in the particular aspects that must focus on the production of knowledge in a doctoral thesis. To mode of conclusion, is considerate the relevance of the investigative competences, as a pivotal element for the production of a doctoral thesis.